Analisis Inflasi di Indonesia (Suatu Pendekatan Model Dinamik) - Afrizal, Afrizal (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
This study aims to determine the magnitude of the effect of the money supply, the exchange rate of rupiah (exchange rate) and the interest rate on inflation in Indonesia during the period 2000.12016.4. The analysis tools used for this research data are: unit root test, integration degree test, cointegration test, error correction model / ECM. The results showed that all staioner research data at level 1 (first difference) based on cointegration test showed that the variables observed in this study co-integration or have long-term relationship. The ECM model used is valid, as indicated by the error correction term (ECT) coefficient is significant. In the short run the money supply, the exchange rate of rupiah (exchange rate) and the interest rate is not significant to the inflation rate, but in the long term is significant.